Alocaç\~ao de portfólio da poupança para aposentadoria no Brasil: Um estudo de caso para fundos fechados de pens\~ao - Marco Antonio C. da Silveira; Tatiana Coimbra Castello Branco (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper contributes for an initial study on the empirical determinants of the portfolio allocation of retirement savings in Brazil. To this end, the work makes use of a database with disaggregated data on the allocation profile of employees participating in the closed pension fund of a major Brazilian company. The results are compared with the recent advances in the theory of portfolio allocation to long-term investors, according to which the allocation of financial wealth between risky assets depends not only on the degree of risk aversion, but also on the other demographic, social and economic variables.
Keywords: G11; 330; Altersvorsorge; Pensionskasse; Brasilien